Science Behind the Blinds: Scientist and Society in The Invisible Man - Steve McLean (Cahiers Victoriens et Edouardiens)
This article examines The Invisible Man in the context of Wells’s educational and scientific writings of the early 1890s. The insular inhabitants of Iping village are unable to comprehend Griffin’s invisible persona—which reiterates the emphasis on the necessity of teaching scientific method in Wells’s educational journalism. The novel’s didactic purpose in highlighting the importance of broadening the public understanding of science is related to John Tyndall’s work on the scientific imagination. Wells’s position in The Invisible Man is also that scientists should endeavour to communicate their ideas as widely as possible. Griffin’s unwillingness to do so is understood in the context of ‘Popularising Science,’ an article in which Wells outlines the mistakes made by men of science who refuse to popularise their subject matter. Griffin’s eventual alienation from society is understood both as a consequence of the public inability to grasp scientific thinking and his own reticence to communicate.